2023
DOI: 10.1007/s00167-023-07404-0
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral arthroplasty with onlay prosthesis leads to higher rates of osteoarthritis progression than inlay design implants: a systematic review

Abstract: Purpose The aim of this study was to report the clinical and functional outcomes, complication rates, implant survivorship and the progression of tibiofemoral osteoarthritis (OA), after new inlay or onlay patellofemoral arthroplasty (PFA), for isolated patellofemoral OA. Comparison of different implant types and models, where it was possible, also represented one of the objectives. Methods A systematic literature search following PRISMA guidelines was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Clinically, this study showed how PFJ can be equated with TKA in survival outcomes and subjective clinical scores and highlighted that PFJ remains a procedure with less blood loss, shorter hospital stay [7], preservation of bone stock and ligaments [23] and better functional outcomes and stair-climbing abilities [17].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, this study showed how PFJ can be equated with TKA in survival outcomes and subjective clinical scores and highlighted that PFJ remains a procedure with less blood loss, shorter hospital stay [7], preservation of bone stock and ligaments [23] and better functional outcomes and stair-climbing abilities [17].…”
Section: Discussionmentioning
confidence: 99%
“…This advancement mitigates trochlear internal rotation risk and effectively manages any degree of dysplasia demonstrating a tangible impact on reducing failure rates [ 16 , 38 , 39 ]. However, these implants can’t effectively substitute the native trochlea, accelerating the progression of OA, which persist as great cause of failure [ 40 42 ]. Moreover, 2nd generation PFAs often result in an increased thickness of the trochlea, causing overstuffing of the patellofemoral joint and, consequently, pain due to increased tension exerted on the retinacular fibers [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“… 9 The new inlay design better maintains the natural biomechanics of the joint and allows personalized and anatomic trochlear resurfacing, reducing complications, improving stability, preserving soft tissue tension, and minimizing overstuffing. 9 , 10 , 11 , 12 , 13 , 14 …”
mentioning
confidence: 99%